Methylphenidate improves learning impairments and hyperthermia‐induced seizures caused by an Scn1a mutation. Issue 10 (25th August 2014) - Ohmori, Iori; Kawakami, Nozomi; Liu, Sumei; Wang, Haijiao; Miyazaki, Ikuko; Asanuma, Masato; Michiue, Hiroyuki; Matsui, Hideki; Mashimo, Tomoji; Ouchida, Mamoru
Summary Objective Developmental disorders including cognitive deficit, hyperkinetic disorder, and autistic behaviors are frequently comorbid in epileptic patients with SCN1A mutations. However, the mechanisms underlying these developmental disorders are poorly understood and treatments are currently unavailable. Using a rodent model with an Scn1a mutation, we aimed to elucidate the pathophysiologic basis and potential therapeutic treatments for developmental disorders stemming from Scn1a mutations. Methods We conducted behavioral analyses on rats with the N1417H‐Scn1a mutation. With high‐performance liquid chromatography, we measured dopamine and its metabolites in the frontal cortex, striatum, nucleus accumbens, and midbrain. Methylphenidate was administered intraperitoneally to examine its effects on developmental disorder–like behaviors and hyperthermia‐induced seizures. Results Behavioral studies revealed that Scn1a‐mutant rats had repetitive behavior, hyperactivity, anxiety‐like behavior, spatial learning impairments, and motor imbalance. Dopamine levels in the striatum and nucleus accumbens in Scn1a‐mutant rats were significantly lower than those in wild‐type rats. In Scn1a‐mutant rats, methylphenidate, by increasing dopamine levels in the synaptic cleft, improved hyperactivity, anxiety‐like behavior, and spatial learning impairments. Surprisingly, methylphenidate also strongly suppressed hyperthermia‐induced seizures. Significance Dysfunction of the mesolimbic dopamine reward pathway may contribute to the hyperactivity and learning impairments in Scn1a‐mutant rats. Methylphenidate was effective for treating hyperactivity, learning impairments, and hyperthermia‐induced seizures. We propose that methylphenidate treatment may ameliorate not only developmental disorders but also epileptic seizures in patients with SCN1A mutations.